An efficient phthalate ester-degrading Bacillus subtilis: Degradation kinetics, metabolic pathway, and catalytic mechanism of the key enzyme. (15th March 2021) - Xu, Youqiang; Liu, Xiao; Zhao, Jingrong; Huang, Huiqin; Wu, Mengqin; Li, Xiuting; Li, Weiwei; Sun, Xiaotao; Sun, Baoguo
Abstract: Phthalate ester pollution in the environment and food chain is frequently reported. Microbial treatment is a green and efficient method for solving this problem. The isolation and systematic investigation of microorganisms generally recognized as safe (GRAS) will provide useful resources. A GRAS Bacillus subtilis strain, BJQ0005, was isolated from Baijiu fermentation starter and efficiently degraded phthalate esters (PAEs). The half-lives for di-isobutyl phthalate, di-butyl phthalate and di-(2-ethylhexyl) phthalate were 3.93, 4.28, and 25.49 h, respectively, from the initial amount of 10 mg per 10 mL reaction mixture, which are records using wild-type strains. Genome sequencing and metabolic intermediate analysis generated the whole metabolic pathway. Eighteen enzymes from the α/β hydrolase family were expressed. Enzymes GTW28_09400 and GTW28_13725 were capable of single ester bond hydrolysis of PAEs, while GTW28_17760 hydrolyzed di-ester bonds of PAEs. Using molecular docking, a possible mechanism affecting enzymatic ester bond hydrolysis of mono-butyl phthalate was proposed of GTW28_17760. The carboxyl group generated by the first hydrolysis step interacted with histidine in the catalytic active center, which negatively affected enzymatic hydrolysis. Isolation and systematic investigation of the PAE degradation characteristics of B. subtilis will promote the green and safe treatment of PAEs in the environment and food industry. Graphical abstract: Image 1 Highlights: Record efficiency was achieved for phthalate ester degradation by strain BJQ0005. Whole metabolic pathway was proposed using genome sequence and intermediate analysis. Three hydrolases were identified with one di-ester bond hydrolysis enzyme. Mechanism affecting enzymatic ester hydrolysis of mono-ester phthalate was proposed.